Progressive Muscle Relaxation (PMR) Training to Improve Mental Health of COVID-19 Survivors at Tanjung Medang Health Center - NURFI PRATIWI; RAHMAT AZHARI KEMAL; ARFIANTI ARFIANTI; RINA AMTARINA (Tazkia Islamic University College, 2026)
Despite being declared cured, some of the patients recovering from COVID-19 experience sequelae that last weeks or months. This situation can increase the risk of mental health, one of which is anxiety disorders. One therapy in overcoming anxiety problems is doing progressive muscle relaxation exercises. Progressive muscle relaxation training is an active technique that involves participants actively contracting muscles to create relaxation by progressively relaxing them. In August of 2022, a series of activities were implemented for individuals who had survived COVID-19 in the North Rupat District of the Bengkalis Regency. Participants included patients who had been previously diagnosed with COVID-19 of various ages and were currently experiencing sequelae of COVID-19 such as anxiety. Participants were given counseling about mental health after COVID-19. After that, the survivors were demonstrated and invited to participate in practicing progressive muscle relaxation (PMR) exercises. The DASS score before activity indicated 20% of the survivors who attended experienced anxiety. After the counseling and training, there was an increase in knowledge regarding the average post-test score of 92 compared to the average pre-test score of 65. This PMR knowledge is expected to be practiced sustainably by the community to improve mental health. Keywords: Anxiety; COVID-19; Mental health; Progressive muscle relaxation training; Survivors